Synthesis of novel plasticizer ester end-capped oligomeric lactic acid and its plasticizing performance in poly(vinyl chloride). (14th June 2021) - Zhang, Zheming; Jiang, PingPing; Liu, Dekai; Feng, Shan; Leng, Yan; Zhang, Pingbo; Haryono, Agus; Li, Zhenhua; Li, Yuchao
Abstract : In this work, a novel high efficiency plasticizer, an ester-capped oligomeric lactic acid mixture (EOL), was successfully synthesized by a two-step esterification reaction, with l -lactic acid as the main raw material. Abstract : With increasing attention to the environment and health, the demand for environmentally friendly plasticizers, which were applied to produce phthalate-free flexible poly(vinyl chloride) (PVC), is becoming more and more urgent. In this work, a novel high efficiency plasticizer, an ester-capped oligomeric lactic acid mixture (EOL), was successfully synthesized by a two-step esterification reaction, with l -lactic acid as the main raw material. The structure of EOL was characterized by using FT-IR, 1 H NMR and time of flight mass spectrometry (TOF-MS). The plasticizing performance of EOLs in PVC was tested and compared with those of commercial environmental plasticizers acetyl tributyl citrate (ATBC) and di-2-ethylhexyl terephthalate (DOTP). According to the results of tensile tests, the elongation at break of PVC plasticized by 50 phr EOLs reached 725.5%, indicating its superior mechanical properties. The result of TGA showed that the thermal stability of PVC plasticized by EOLs was as comparable as that of PVC plasticized by DOTP or ATBC. Furthermore, compared with ATBC and DOTP, EOLs showed better migration resistance in the leaching test. All test results showed that the comprehensive performance of EOLs was better than those of commercial green plasticizers ATBC and DOTP, which provided a new method for the development of novel green plasticizers.